Proses Atensi Pengetahuan pada Siswa Attention Deficit Hyperactivity Disorder (ADHD) dalam Memecahkan Masalah Matematika Materi Aritmetika Sosial - Andri Mahardhika Birda; Kamid Kamid; M. Rusdi (Universitas Jambi, 2016)
Attention process is a part of or a small part in memorizing phase with in a thinking process. This research is a qualitative research uses a descriptive qualitative research method. This research aims to describe knowledge attention process of ADHD students. The data was collected by interview and modified thinking aloud methods. At the step of attention looking for and understanding problem in attention process, SADHD was able to observe and determine the adequacy of data. However, at the stage of strategic planning, SADHD experienced a difficulty. At the stage of exploring solution, SADHD also experienced difficulty. At the stage of thinking and redefining, SADHD was able to check and convince the result.